A newly identified interaction between nucleolar NPM1/B23 and the HTLV-I basic leucine zipper factor in HTLV-1 infected cells - Liu, Zhenlong; Larocque, Émilie; Xie, Yongli; Xiao, Yong; Lemay, Guy; Peloponese, Jean-Marie; Mesnard, Jean-Michel; Rassart, Éric; Lin, Rongtuan; Zhou, Shuang; Zeng, Yiming; Gao, Hongzhi; et al. (Frontiers in Microbiology, 2022)
Human T-cell leukemia virus type 1 is the causative agent of HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP) and adult T-cell leukemia-lymphoma (ATL). The HTLV-1 basic leucine zipper factor (HBZ) has been associated to the cancer-inducing properties of this virus, although the exact mechanism is unknown. In this study, we identified (nucleophosmin) (NPM1/B23) as a new interaction partner of the major sHBZ isoform. We show that sHBZ and the less abundant uHBZ isoform interacts with nucleolar NPM1/B23 in infected cells and HTLV-1 positive patient cells, unlike equivalent antisense proteins of related non-leukemogenic HTLV-2, -3 and -4 viruses. We further demonstrate that sHBZ association to NPM1/B23 is sensitive to RNase. Interestingly, sHBZ was shown to interact with its own RNA. Through siRNA and overexpression experiments, we further provide evidence that NPM1/B23 acts negatively on viral gene expression with potential impact on cell transformation. These results suggest that the interaction of NPM1/B23 with sHBZ impact regulation of viral gene expression (including its own) and could contributes to the role of this viral protein in ATL development. Our results hence provide a new insight over HBZ-binding partners in relation to cellular localization and potential function on cell proliferation and should lead to a better understanding of the link between HBZ and ATL development.